2002
DOI: 10.1116/1.1508802
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and properties of Ti–Si–N nanocomposite films

Abstract: Ti-Si-N nanocomposite films were deposited by multitarget reactive magnetron sputtering. Energy dispersive spectroscopy, X-ray diffraction, transmission electron microscopy, and x-ray photoelectron spectroscopy were employed to characterize their microstructure and a microhardness tester was used to measure their hardness. The influence of substrate temperature on these films was investigated, too. The results reveal that the films consist of TiN and Si 3 N 4 . Si 3 N 4 exists as amorphous, which strongly prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 16 publications
6
34
0
Order By: Relevance
“…44 The values of V 0 , B 0 , and B 0 Ј obtained for the fcc͑NaCl͒-TiN and hcp͑ß͒-Si 3 N 4 are in good agreement with experimental results and calculated values reported in the literature. 26 The calculated values of the hypothetical fcc͑NaCl͒-SiN, which has been observed only as heteroepitaxially stabilized 1-2 ML thick interface in TiN/SiN/TiN heterostructures, [13][14][15][16] could not be compared with experimental data. Nevertheless, our calculated value of the first derivative of the bulk modulus, B 0 Ј, of this phase of about 4 is within the range predicted by the universal binding-energy relation.…”
Section: Computational Methods Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…44 The values of V 0 , B 0 , and B 0 Ј obtained for the fcc͑NaCl͒-TiN and hcp͑ß͒-Si 3 N 4 are in good agreement with experimental results and calculated values reported in the literature. 26 The calculated values of the hypothetical fcc͑NaCl͒-SiN, which has been observed only as heteroepitaxially stabilized 1-2 ML thick interface in TiN/SiN/TiN heterostructures, [13][14][15][16] could not be compared with experimental data. Nevertheless, our calculated value of the first derivative of the bulk modulus, B 0 Ј, of this phase of about 4 is within the range predicted by the universal binding-energy relation.…”
Section: Computational Methods Usedmentioning
confidence: 99%
“…It collapses and becomes amorphous at a greater thickness. [13][14][15] This is due to the inherent instability of this material as shown by ab initio DFT calculations 23 and by more recent calculations of the phonondispersion curves. 24 Furthermore, the thermodynamic studies [25][26][27] showed that the Gibbs free energy of the reaction 3SiN+ 0.5N 2 =Si 3 N 4 , which corresponds to a sufficiently large activity of nitrogen, is −168 kJ/ mol atom ͑see also remark Ref.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Multilayers are useful as model systems since they allow the design and study of interfaces not readily accessible in three-dimensional nanocomposite. Recently, TiN/SiN x multilayer coatings have been synthesized, and hardness maxima of 33-40 GPa have been reported for fcc-TiN/SiN x /TiN heterostructures when SiN x was about 1-2 monolayer (ML) thick [3,4,[7][8][9][10]. The possible structure of SiN x layers in multilayer coatings is not completely understood.…”
Section: Introductionmentioning
confidence: 98%
“…The possible structure of SiN x layers in multilayer coatings is not completely understood. It was first considered as amorphous of effectively X-ray amorphous, but the possibility of crystalline structures was also shown [3,4,[7][8][9][10] when the thickness of SiN x layers was less than a critical value because of the "template effect" of TiN layers. The phase transformation for SiN x from amorphous to * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%